Kepastian Hukum Perjanjian Perkawinan Yang Tidak Didaftarkan (Studi Kasus Putusan No. 1718/PDT.G/2021/PA. BTM) - Nicholas Waisaka Aditio; Mia Hadiati (Universitas Ekasakti, 2024)
Everything regarding marriage that has been regulated is a binding provision and must be stipulated for members of society. The legal consequences of divorce is regulated in Article 37 of Law Number 1 of 1974 regarding Marriage. In the verdict the author uses as research material, Verdict Number 1718/Pdt.G/2021/PA. Btm has determined based on the Supreme Court jurisprudence Number: 3405/K/PDT/2012 which confirms that marriage agreements that aren’t registered has no legal force. The author’s goal is to determine the legal consequences of unregistered marriage agreements. The author uses written materials as main sources to analyze with the results of interviews. The results of the research by the author is that the Verdict Number 1718/Pdt.G/2021/PA. Btm has to be cancelled because the jurisdiction verdict number 3405/K/PDT/2012 has been cancelled and the marriage agreement between Nurevi binti Muhammad Mubazzir and Andrew Kevin Plant should be a permenant legal force. The conclusion of the research is after the issuance of Constitutional Court Decision No. 69/PUU-XIII/2015, a marriage agreement is no longer interpreted only as an agreement made before marriage, but also made during marriage.